Analysis Of Pharmaceutical Personnel Needs On Workload With Method Wisn (Workload Indicator Of Staffing Need) In Hospital Pharmaceutical Installation Hospital Royal Prima - Ary Denggan Syahputra Lubis; Ermi Girsang; Maya Sari Mutiara; Ulina Karo-karo (CV. Inara, 2022)
Hospital Pharmacy Installation (IFRS) is a function implementing unit that organizes all pharmaceutical service activities in hospitals (Permenkes, 2016). Hospital pharmacy services are one of the activities in hospitals that support quality health services. This is clarified in the Decree (SK) of the Minister of Health Number: 1333/Menkes/SK/XII/1999 concerning Hospital Service Standards, stating that hospital pharmacy services are an inseparable part of the hospital health care system that is patient-oriented, providing medicines, including clinical pharmacy services, which are affordable for all levels of society. This study aims to determine the need for health workers by calculating the ideal number of pharmacists based on the workload at the Hospital Royal Prima . This research is qualitative research using observation techniques, interview guidelines and document review. This study uses research informants where the informants used are the head pharmacist and pharmacist. Data analysis is the process of systematically searching and compiling data obtained from the results of field observations (work sampling), in-depth interviews and document reviews. From the results of research conducted that pharmaceutical workers use 85.3% of their working time with productive activities. Of the productive activities as much as 40.2% are direct productive activities while the rest are indirect productive activities, and as much as 23.8% of indirect productive activities are administrative activities, because in this study 8.7% were obtained as nonproductiveactivities and personal activities with the results of work sampling with the WINS method, it turns out that the number of pharmacists installed at the Hospital Royal Prima Marelan is smaller than the need for pharmaceutical workers installed at the Hospital Royal Prima Marelan.